Respuesta :

7x+3y=25
-2x-y=-8

7x+3y=25
(-2x-y=-8)3

7x+3y=25
-6x-3y=-24
x. =1

x=1

now you plug in that x value

-2(1)-y=-8
-2-y=-8
+2. +2
-y = -6
-1. -1
y = 6


(1,6)

Answer:

x=1 , y=6

Step-by-step explanation:

7x+3y = 25

-2x-y = -8

Multiply the second equation by 3 so we can eliminate y

3(-2x-y )= -8*3

-6x -3y = -24

Add this equation to the first equation

-6x -3y = -24

7x+3y = 25

----------------------

x = 1


But we still need to find y by substituting x =1

-2x -y = -8

-2(1) -y = -8

-2-y = -8

Add 2 to each side

-2+2 = -8+2

-y = -6

Multiply by  -1

y = 6